2007
DOI: 10.1590/s0103-90162007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall intensity and Mepiquat Chloride persistence in cotton

Abstract: In some regions where cotton is grown in Brazil rainfall amounts to about 2,000 mm per year, which imposes a great risk for Mepiquat Chloride (MP) to be washed from cotton leaves before being absorbed. The objective of this research was to evaluate the MC persistence when applied on cotton plants submitted to different rain intensities after spraying. The treatments were three MC rates: 0, 15.0 and 30.0 g a.i. ha -1 and four simulated rainfalls, applied 90 minutes after MC spraying: 5, 10, 20 and 40 mm, plus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
3
16
0
1
Order By: Relevance
“…However, no differences were observed when the results obtained for plants treated with PGR were compared with the control. Similar finding was reported by Souza and Rosolem (2007) when they applied mepiquat chloride and simulated rainfall after 90 min and the number of cotton reproductive structures was not affected. Effects of these growth regulators on fruit retention have been inconsistent.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…However, no differences were observed when the results obtained for plants treated with PGR were compared with the control. Similar finding was reported by Souza and Rosolem (2007) when they applied mepiquat chloride and simulated rainfall after 90 min and the number of cotton reproductive structures was not affected. Effects of these growth regulators on fruit retention have been inconsistent.…”
Section: Resultssupporting
confidence: 88%
“…Thus, smaller plant height and dry matter production were observed even without the complete absorption of the growth regulators. Similar results were found by Souza and Rosolem (2007), but Mateus et al (2004) observed a compensatory gain due to leaf thickening and an increased leaf area, despite the reduced height after the application of mepiquat chloride, which did not affect cotton plant dry matter. Total growth of cotton plants measured between the application of the regulators and plot disassembly was larger when mepiquat chloride was applied (Table 4).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations